Patubas the Western Rice Research and Farmer's Training and Livelihood Complex - Arancillo, Urien F. (College of Architecture, University of the Philippines Diliman, 2019)
With the Philippines being a predominantly agricultural-dependent country, focusing in rice, the government granted a priority in its research and development. An upgrade in the country's rural infrastructures was found to be critical to the overall agricultural development. But currently, most of the current rice research facilities are concentrated in the Luzon area and with Western Visayas being the third highest palay producer among the regions, it should also be connected to the leading institutions to further promulgate its continued development. The provision of modern R&D (research and development) facilities is a key point in the efficient and effective generation of marketable technologies. "Patubas : the Western Visayas Rice Research and Farmers' Training and Livelihood Complex" proposes a design for a rice research and farmers' training and livelihood complex in Oton, Iloilo which will be a congregation of spaces that will serve to address the several agendas on research, education and community development. It is a venue where scientists can work and collaborate in a high tech environment to support and make agricultural advancements in the field of rice research and interact with the different target users respectively. Farmers will be given the opportunity to train, learn and interact in the development to further facilitate the improvement of each of their livelihood. The project aims to serve as a bridge in connecting the leading institutions in the country to further promulgate the continued development in rice research and strengthen the livelihood of the present site community.